2018
DOI: 10.1093/jeg/lby020
|View full text |Cite
|
Sign up to set email alerts
|

The development push of refugees: evidence from Tanzania

Abstract: The International Food Policy Research Institute (IFPRI), established in 1975, provides evidence-based policy solutions to sustainably end hunger and malnutrition and reduce poverty. The institute conducts research, communicates results, optimizes partnerships, and builds capacity to ensure sustainable food production, promote healthy food systems, improve markets and trade, transform agriculture, build resilience, and strengthen institutions and governance. Gender is considered in all of the institute's work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 91 publications
(59 reference statements)
1
46
0
Order By: Relevance
“…The literature suggests that, if anything, refugee camps reduce out-migration [21,25,26,29]. Nevertheless, in order to rule out native displacement as an underlying driver of the refugee effect on vegetation, we also evaluate how refugees may change population and builtup area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that, if anything, refugee camps reduce out-migration [21,25,26,29]. Nevertheless, in order to rule out native displacement as an underlying driver of the refugee effect on vegetation, we also evaluate how refugees may change population and builtup area.…”
Section: Resultsmentioning
confidence: 99%
“…Refugee camps offer additional sources of cheap labor and attract capital investment, such as the expansion of road networks [21][22][23][24][25][26][27]. Both features can strengthen farmers' access to cheaper inputs and auxiliary output markets reinforcing incentives to cultivate more land [28][29][30]. However, refugees themselves have at times been responsible for the conversion of forest to agriculture due to their volition to continue farming in host regions [28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even in a globalizing world, the proximity of large and affluent cities and regions still matters (Head and Mayer ). Even less expected, the presence of refugee camps seems to generate a lasting and positive impact on the welfare of the hosting population (Maystadt and Duranton ). The gathering of refugees in a camp would thus generate effects akin to what we call agglomeration effects.…”
Section: Why Do Cities Exist?mentioning
confidence: 99%
“…Different versions of this refugee shock have been used in other papers (e.g. Baez 2011: Maystadt 2011Maystadt and Duranton 2014;Maystadt and Verwimp 2014;Vargas-Silva 2015, 2016). As shown in Figure 5, there is a substantial range of values for the shock variable.…”
Section: Estimationsmentioning
confidence: 99%
“…Baez (2011) found that the refugee shock resulted in a worsening of Tanzanian child anthropometrics and an increase in their incidence of infectious diseases. On the other hand, Maystadt (2011) and Maystadt and Duranton (2014) found that the refugee inflow improved the welfare of the hosting population by reducing poverty and transport costs as a result of increased road building. Maystadt and Verwimp (2014) found heterogeneous effects of the refugee shock.…”
Section: Introductionmentioning
confidence: 99%